2012
DOI: 10.3136/fstr.18.593
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Collagen-Derived Oligopeptide Prolylhydroxyproline on Differentiation of Mouse 3T3-L1 Preadipocytes

Abstract: Beneficial effects of collagen peptide ingestion to reduce serum triacylglycerides have been reported, suggesting that the physiological conditions of adipocytes are modulated following collagen peptide ingestion. In this study, the effects of prolylhydroxyproline, a major digestive product of ingested collagen peptide in the blood, on the differentiation of mouse 3T3-L1 preadipocytes in vitro were investigated. 3T3-L1 preadipocytes were induced to differentiate to adipocytes and treated with prolylhydroxyprol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 18 publications
1
10
0
Order By: Relevance
“…In addition, we demonstrated that Pro‐Hyp and Hyp‐Gly stimulate the growth of mouse skin fibroblasts on collagen gels . Minaguchi et al . reported that Pro‐Hyp reduces the size of droplets in mouse 3 T3‐L1 preadipocytes.…”
Section: Introductionsupporting
confidence: 53%
“…In addition, we demonstrated that Pro‐Hyp and Hyp‐Gly stimulate the growth of mouse skin fibroblasts on collagen gels . Minaguchi et al . reported that Pro‐Hyp reduces the size of droplets in mouse 3 T3‐L1 preadipocytes.…”
Section: Introductionsupporting
confidence: 53%
“…In addition, Pro-Hyp may affect TG metabolism, since it can modulate adipocyte differentiation. Specifically, the size of lipid droplets was found to be significantly smaller in differentiated mouse 3T3-L1 preadipocytes than in cells treated with a mixture of proline and hydroxyproline or in untreated cells (Minaguchi et al, 2012). However, further studies are required to elucidate the role of Pro-Hyp in blood lipid profiles.…”
Section: Discussionmentioning
confidence: 99%
“…Two hundred ng/ml Pro-Hyp was added to the medium every 2 days according to the method established by Minaguchi et al . [25]. The effects of Pro-Hyp on proliferation of cultured cells, morphology and number of LDs and mitochondria, and concentration of triglycerides in SVCs were evaluated on days 1, 3, 5, 7 and 8.…”
Section: Methodsmentioning
confidence: 99%
“…Pro-Hyp has been shown to stimulate the growth of mouse skin fibroblasts on collagen gels [37] and to modulate osteoarthritis induced by a high phosphorus diet in rat [27]. In addition, we previously reported that ingestion of Pro-Hyp alters the metabolic state of 3T3-L1 cells [25]. 3T3-L1 cells derived from mouse embryo fibroblasts undergo a highly conserved and efficient program of adipogenesis in culture and upon transplantation in vivo [17].…”
mentioning
confidence: 99%